Comparison Study Of Determination Of Field Cbr Values With Angkur And Dcp Equipment In Road Subgrade For Surabaya Road Development Planning - Berlian Farahdiza Hertanti; Agus Tugas Sudjianto; Aji Suraji; Candra Aditya (CV. Creative Tugu Pena, 2026)
This study aims to evaluate the carrying capacity of the subgrade in the construction of road pavement by comparing the value of the California Bearing Ratio (CBR) of the field obtained from the CBR Angkur and Dynamic Cone Penetrometer (DCP) test. The quality of the subgrade is a crucial factor in determining stability and age of road pavement service, but often there are significant variations in the results of testing the carrying capacity of the soil between different methods. This study was conducted on Jl. Baruk Utara III, Kedung Baruk, Rungkut District, Surabaya, by collecting primary data from testing the physical and mechanical properties of the soil in the laboratory, as well as the CBR Angkur and DCP testing in the field. The results showed that the soil at the study site was classified as silt (OL) and A-4, with high water content (59.14%) and low plasticity, indicating weak carrying capacity. The CBR value of the field of the Angkur test is 2.53%, while the CBR design value of the DCP test ranges from 3.13%. Although there are numerical differences, the two methods consistently show that the subgrade has a low carrying capacity. This conclusion confirms the need for soil stabilization to ensure optimal and sustainable pavement performance.